On New Trends in the Studies of the History of the Mongol Conquests: Based on the Example of Stephen Pow’s Article “The Last Campaign and Death of Jebe Noyan” - D.M. Timokhin; V.V. Tishin (Золотоордынское обозрение)
Research objectives: A recently published brilliant article by Stephen Pow, “The Last Campaign and Death of Jebe Noyan,” opened a discussion on a number of issues related to the Mongol campaigns in the territory of Caucasus and Eastern Europe in the first half of the 1220s. In particular, the author defends the thesis that the raid of the army led by Jebe Noyan and Sübe’etei Ba’atur was intended as a conquest. He also hypothesizes that the death of the first of the aforementioned generals occurred during that campaign, specifically in the Battle of the Kalka River against the Kipchak and Russian Princes’ troops. The authors of this article cannot agree with the arguments of the Hungary-based scholar and attempt to bring a number of counter-arguments against both of his positions. Research materials: The authors tried to use the whole array of available written sources to make adjustments to the solution of the questions raised by S. Pow. First of all, these are the works of Persian authors (al-Nasavi, Juvayni, Rashid al-Din al-Tabib), the “Georgian Chronicle of a Hundred Years”, the “Chronicle” written in Armenian by Mxitar Airivanetsi, Old Russian Chronicles (foremost among them, the Novgorod First Chronicle, Laurentian Chronicle and Sofia First Chronicle). In addition, linguistic materials represented by the data of the Turkic, Mongolian and Slavic languages were used too. Research results and novelty: The fact that Stephen Pow did not use all available sources is the main counterargument against the assertion about the conquering nature of the Mongol military campaign. In addition, it is not possible to find any direct or indirect data allowing one to support his hypothesis. The interpretation of the death of Jebe Noyan during the Battle of the Kalka River, based on the visionary identification of his name with Gemyabek recorded in Old Russian chronicles, has no linguistic evidence absolutely.